Aurélia de Souza : pelo brilho da penumbra - Pelayo, Raquel, 1968- (2017)
This article explores a new thesis about the life and work of the nineteen century portuguese woman artist, Aurélia de Souza, based on her work “Santo António” that points her as having suffered from tuberculosis and her paintings getting profound sense in the frame of fin-de siècle romanticism. The hypothesis is grounded in the content of other of her important works and facts from her biography